Campylobacter pylori in the upper gastrointestinal tract of patients with HIV-1 infection. - Francis, N D (1990)
Fifty one patients with human immuno-deficiency virus (HIV-1) infection who had been consecutively endoscoped for upper gastrointestinal symptoms were biopsied (stomach or duodenum, or both) and compared with 59 age and sex matched controls for the presence of Campylobacter pylori. In 28 (47%) of the control group but in only seven (14%) of the HIV seropositive patients were C pylori seen on histological examination (p less than 0.001, odds ratio 5.6, 95% confidence interval 2.2-14.5). Sixteen patients who were HIV antibody positive had other index diseases for the diagnosis of AIDS in the biopsy material and, when these were excluded, comparison with the control group still showed a significant difference; p less than 0.01, odds ratio 3.6, 95%, confidence interval 1.4-9.6. In this series, therefore, C pylori were far less common in HIV antibody positive patients than in controls. Among the HIV positive patients, a higher proportion of C pylori negative cases had AIDS but this trend was not significant. The findings of this study indicate that whatever abnormalities of cell mediated mucosal immunoregulation are caused by HIV infection, they do not seem to be important in the response to infection by C pylori.